A Community-Level Knowledge, Attitude, and Practice about Dengue Fever and the Identification of Mosquito Breeding Containers in Dire Dawa City of Ethiopia: A Cross-Sectional Study - Taye Kebede; Bedasa Tesema; Akalu Mesfin; Dejene Getachew (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Lately, dengue fever (DF) is an emerging viral disease, one of the top 10 threats to global health, causing 24 million–130 million symptomatic cases and 10,000–50,000 deaths yearly. DF threat has expanded beyond traditional areas of endemicity, with over 50% of the world population now estimated to live in areas at risk of dengue virus (DV) transmission. Hence, the current study aimed to assess the community’s knowledge, attitude, and practice about DF transmission and its prevention and to identify mosquito breeding containers in Dire Dawa City, Ethiopia. Methods. A household-based cross-sectional study was conducted from February to September 2022. A semistructured questionnaire was used to collect data. Immature stages of mosquitoes were collected from human habitations to identify their breeding containers. Both descriptive and inferential statistics were used to analyze the data. A p value of <0.05 was used to declare a significant association between variables at a 95% level of confidence. Results. About 95.1% of respondents had information about DF, where the majority (58.0%) heard from relatives, friends, and families and 43.3% from health professionals. Only 17.9% knew DF was caused by viruses. Around 83%, 79%, and 50.8% of respondents knew that fever, headache, and back pain are the sign and symptoms of DF, respectively. Sadly, only 4.2% knew that DF vectors bite during day time and 10.5% of respondents did not know DF transmission season. The majority (80.5%) of respondents knew that DF is a preventable disease. Totally, 6,853 water-holding containers were identified, out of this 77% were jerrycans and 14.1% were barreled. Out of the identified water-holding containers, 7.73% were positive for mosquito larvae/pupae. House index (HI), container index (CI), and Breteau index (BI) were 19.5, 8.38, and 45.14, respectively. Conclusion. The majority of the community members has no awareness of the DF vectors, time of bites, pick transmission season, and their protection mechanisms. The habit to store water in and around habitation was prevalent. Hence, programmed and institutionalized awareness is mandatory for the control and prevention of DF and its vectors and for breaking the transmission cycle in Dire Dawa communities.